HUBUNGAN INDEKS MASSA TERHADAP KELINCAHAN ANAK USIA 11-12 TAHUN DI SEKOLAH SEPAK BOLA SIAGA PRATAMA BOJONG GEDE KABUPATEN BOGOR - Prayoga Windu Laksana (2022)
Background: Agility is the body's ability to change direction with speed when moving without losing balance in its actual position. Body composition is also very influential in a child's agility because agility plays an important role in physical mobility, but agility is not a single physical component, but is composed of components of coordination, strength, flexibility, reaction time and power. Apart from that, there are also several factors that affect agility, including anthropometry, body type, age, gender, body weight. The purpose of research : This study aims to determine whether there is a relationship between body mass index and the agility of children aged 11-12 years at the Bojong Gede Football School Siaga Pratama, Bogor Regency. Research Method : The method or type of research used in this research is correlational. Correlational research aims to find out whether or not there is a relationship, if so, how close is the relationship and whether the relationship is meaningful or not. This study uses a survey method with test and measurement techniques. The analysis technique in this study uses regression analysis, which is looking for a meaningful relationship between the independent variable and the dependent variable. Results : There is a significant relationship between BMI and agility at the Pratama Siaga Football School with a value of r = 0.550 with a significance value of 0.137 > 0.05. Conclusion: There is a relationship between Body Mass Index (BMI) and agility at the Bojong Gede Football School Siaga Pratama, Bogor Regency.